Computational study on the selective inhibition mechanism of MS402 to the first and second bromodomains of BRD4. Issue 1 (13th November 2018) - Wang, Qianqian; Li, Ying; Xu, Jiahui; Wang, Yuwei; Shi, Danfeng; Liu, Liang; Leung, Elaine Lai‐Han; Yao, Xiaojun
Abstract: As a member of the bromodomain and extraterminal domain (BET) family, BRD4 is considered as a potential target for cancer treatment. However, because of the highly conservation of its two homologous bromodomains (BD1/BD2), selective inhibition of each bromodomain remains a challenge. MS402 is a domain‐selective inhibitor of BRD4‐BD1 over BRD4‐BD2 reported recently. Understanding the selectivity mechanism would be very useful for the further design of more potent BD1‐selectivity inhibitors. Molecular dynamics simulation, adaptive biasing force and multiple‐walker adaptive biasing force were performed to study the inhibition and domain‐selective mechanism of MS402 toward BRD4‐BD1 over BRD4‐BD2 here. Results demonstrate BRD4‐BD1 binds to MS402 with lower binding free energy than BRD4‐BD2. Residues Gln85, Pro86, Asn140, and Ile146 are crucial for MS402's selectively binding to BRD4‐BD1. MS402 needs to overcome more energy barrier to dissociate from BD1 than from BD2 pocket. These findings will be helpful for rational structural modification of existing inhibitors to increase their BD1‐selectivity.